2016
DOI: 10.2196/mental.5801
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an Immersive Virtual Reality Intervention for Hospitalized Patients: An Observational Cohort Study

Abstract: BackgroundVirtual reality (VR) offers immersive, realistic, three-dimensional experiences that “transport” users to novel environments. Because VR is effective for acute pain and anxiety, it may have benefits for hospitalized patients; however, there are few reports using VR in this setting.ObjectiveThe aim was to evaluate the acceptability and feasibility of VR in a diverse cohort of hospitalized patients.MethodsWe assessed the acceptability and feasibility of VR in a cohort of patients admitted to an inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(132 citation statements)
references
References 18 publications
6
125
1
Order By: Relevance
“…In addition, in a feasibility study of VR for hospitalized patients being somewhere else was also found to be a benefit. Here, confirming our findings, a patient described VR provides an 'escape' from the confines and boredom of the hospital room [23].…”
Section: Comparison W I T H P R I or Wo R Ksupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, in a feasibility study of VR for hospitalized patients being somewhere else was also found to be a benefit. Here, confirming our findings, a patient described VR provides an 'escape' from the confines and boredom of the hospital room [23].…”
Section: Comparison W I T H P R I or Wo R Ksupporting
confidence: 90%
“…Together these studies indicate that VR is an effective distracter and a promising non-pharmacological analgesic intervention. Most studies described the use of VR in outpatient settings instead of hospitalized patients [12,22,23]. However, the use of VR at a hospital ward seems feasible and without great side effects [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of VR in hospitalized patients significantly reduced pain versus a controlled distraction condition. These results indicate that VR is an effective and safe adjunctive therapy for pain management in the acute inpatient setting (27).…”
Section: Digital Health Is a Paradigm Shiftmentioning
confidence: 72%
“…This recognition of the potential impact of VR technology has led to the emergence of a significant, albeit still maturing, research literature that documents the many clinical and research targets where VR can add value relative to traditional assessment and intervention methods. A short list of the areas where Clinical VR has been usefully applied includes fear reduction in persons with specific phobias (Morina et al, 2015; Opris et al, 2012; Parsons & Rizzo, 2008; Powers & Emmelkamp, 2008), treatment for posttraumatic stress disorder (Beidel, Frueh, Neer, & Lejuez, 2017; Botella et al, 2015; Difede & Hoffman, 2002; Difede et al, 2007, 2014; Maples-Keller et al, 2017; McLay et al, 2011; Rizzo et al, 2010, 2013, 2017; Rothbaum, Hodges, Ready, Graap, & Alarcon, 2001; Rothbaum et al, 2014), cue-exposure for addiction and relapse prevention (Hone-Blanchet, Wensing, & Fecteau, 2014; Yoon et al, 2014), depression (Falconer et al, 2016), paranoid delusions (Freeman et al, 2016), discomfort reduction in cancer patients undergoing chemotherapy (Schneider, Kisby, & Flint, 2010), acute pain reduction during wound care and physical therapy with burn patients (Hoffman et al, 2011), other painful procedures (Gold et al, 2006; Mosadeghi, Reid, Martinez, Rosen, & Spiegel, 2016), body image disturbances in patients with eating disorders (Riva, 2011), navigation and spatial training in children and adults with motor impairments (John, Pop, Day, Ritsos, & Headleand, 2017), functional skill training and motor rehabilitation in patients with central nervous system dysfunction (e.g. stroke, traumatic brain injury, spinal cord injury, cerebral palsy, multiple sclerosis, etc.)…”
Section: Introductionmentioning
confidence: 99%